Analysis of CAMERA-1 S. aureus Bacteremia Trial Results Using the DOOR. (4th October 2017) - Holland, Thomas L; Davis, Joshua S; Doernberg, Sarah B; Tran, Thuy Tien T; Evans, Scott R; Cosgrove, Sara E; Boucher, Helen W; Corey, G Ralph; Fowler, Vance; Chambers, Henry F; Tong, Steven Y. C
Abstract: Background: Desirability of Outcome Ranking (DOOR) is a novel approach to measure benefits and risks in clinical trials, in which patients are categorized into an overall clinical outcome and ranked with respect to the desirability of that outcome (Evans et al, Clin Infect Dis 2015;61:800–6). A DOOR endpoint specific for S. aureus bloodstream infection (BSI) has previously been developed. We retrospectively applied this endpoint to CAMERA-1, a pilot randomized controlled trial that evaluated the effect of combining flucloxacillin with vancomycin, compared with vancomycin monotherapy, for treatment of MRSA BSI. CAMERA-1 found a trend to benefit for combination therapy in the surrogate endpoint of duration of bacteremia. Methods: Using the S. aureus BSI DOOR endpoint (Figure 1), the 60 CAMERA-1 participants were classified into an ordinal overall clinical outcome. This overall outcome incorporates mortality, treatment failure, infectious complications, and adverse events. The probability of a better rank with combination therapy was estimated. A partial credit approach, which directly assigns a score to each level, was also used to investigate potential outcome differences between treatment groups. Results: The distribution of DOOR by treatment group is shown in Figure 2. The probability of a higher DOOR with combination therapy was 0.47, 95% CI 0.33–0.60, i.e. no evidence of a difference between treatment groups. Assigning a range of partial credit weights to each DOOR category demonstrated how nuanced differences between treatment strategies can be explored. Conclusion: DOOR and partial credit analyses can be used to compare risks and benefits of different management strategies. Using the CAMERA -1 trial data, combination and standard therapy for MRSA BSI were associated with similar DOOR probabilities. These methodologies can inform and be adapted to other studies comparing treatment strategies, including the currently recruiting CAMERA-2 trial. Disclosures: All authors: No reported disclosures.